Genetic drivers of liver cirrhosis: The role of SERPINA1 and PNPLA3 variants in disease onset and progression - Mikolas Holinka; Soňa Fraňková; Svetlana Adamcova Selcanova; Lubomir Skladany; Ondřej Fabián; Martin Kveton; Dusan Merta; Vera Adamkova; Jaroslav A. Hubacek; Veronika Pitova; Sarka Vesela; Tomas Hucl; et al. (PLoS ONE, 2025)
SERPINA1 Z and PNPLA3 G alleles are the most potent genetic risk modifiers in chronic liver disease (CLD) progression. We aimed to test the impact of concomitant carriage of these variants on the progression of CLDs of various aetiology. The cirrhosis cohort included 1583 individuals with CLD, evaluated as candidates for liver transplantation (LTx), with alcoholic-related liver disease (ALD), metabolic dysfunction-associated (MASLD), viral (VIR), autoimmune/cholestatic (AIH-CHOL), and metabolic conditions (MET). This cohort was compared to a control population of 3483 healthy individuals. The frequency of SERPINA1 MZ heterozygotes was significantly higher (p < 0.0001) in the entire cirrhosis group (84/1583; 5.3%) than in controls (89/3483; 2.6%), OR 2.57 (95% CI 1.92–3.44). The frequency of SERPINA1 MZ heterozygotes was significantly higher in the subgroups with ALD and MASLD (37/557; 6.4% and 23/208; 11.1%, respectively, p < 0.0001); the frequency in the subgroups VIR, AIH-CHOL and MET did not differ from controls. The frequency of the PNPLA3 G allele was significantly higher (p < 0.0001) in the entire cirrhosis group (880/1,583; 55.6%) than in controls (1418/3402; 41.6%); OR 1.48 (95% CI 1.36–1.99). The G allele frequency was significantly higher only in ALD, MASLD and VIR subgroups (392/577, 67.9%; 133/208, 63.9% and 139/264, 52.7%; p < 0.0001, 0.0001 and 0.0005, respectively). The frequency of the PNPLA3 G allele was the same in cirrhotic patients carrying SERPINA1 MM and MZ genotypes (824/1483, 55.6% vs 50/84, 59.2%, N.S.). SERPINA1 MZ heterozygotes with ALD and MASLD were significantly younger (56.9 vs 60 years, p = 0.046) and had a higher MELD score (17 vs 15 points, p = 0.0003) at waitlisting, whereas the PNPLA3 genotype had no impact on the age and MELD score at waitlisting. We conclude that both variant alleles increase the risk of liver cirrhosis in ALD and MASLD; however, SERPINA1 MZ heterozygotes have more progressive chronic liver disease and need LT at a younger age.